Foundations of reading comprehension in children with intellectual disabilities. (January 2017) - van Wingerden, Evelien; Segers, Eliane; van Balkom, Hans; Verhoeven, Ludo
Abstract: Background: Knowledge about predictors for reading comprehension in children with intellectual disabilities (ID) is still fragmented. Aims: This study compared reading comprehension, word decoding, listening comprehension, and reading related linguistic and cognitive precursor measures in children with mild ID and typically developing controls. Moreover, it was explored how the precursors related to reading achievement. Method and procedures: Children with mild ID and typical controls were assessed on reading comprehension, decoding, language comprehension, and linguistic (early literacy skills, vocabulary, grammar) and cognitive (rapid naming, phonological short-term memory, working memory, temporal processing, nonverbal reasoning) precursor measures. It was tested to what extent variations in reading comprehension could be explained from word decoding, listening comprehension and precursor measures. Outcomes and results: The ID group scored significantly below typical controls on all measures. Word decoding was at or above first grade level in half the ID group. Reading comprehension in the ID group was related to word decoding, listening comprehension, early literacy skills, and temporal processing. Conclusion and implications: The reading comprehension profile of children with mild ID strongly resembles typical early readers. The simple view of reading pertains to children with mild ID, with additional influence of early literacy skills and temporal processing.